PENYIMPANGAN EJAAN YANG DISEMPURNAKAN PADA SURAT LAMARAN KERJA MAHASISWA IKIP PGRI MADIUN (STUDI ANALISIS KESALAHAN BERBAHASA) - Ermi Adriani Meikayanti; Muhammad Binur Huda (Widyabastra : Jurnal Ilmiah Pembelajaran Bahasa dan Sastra Indonesia, 2014)
There are many errors on Job Application Letter (JAL) as task of lecture. The errors can be analizyzed based on EYD which consist of letters, words, and punctuations. Specifically, this research aims at explaining the errors of using letters, words, and punctuations on JAL for the students of IKIP PGRI Madiun. This research is descriptive qualitative explaining the phenomena occurred on JAL of IKIP PGRI Madiun students. The qualitative data research and primary data source research are gained using writing document technique of students JAL. The validation data technique used are method and experts triangulations. The technique of data analysis is using interactive model analysis. The result of this research shows that there are 25 similar errors of students JAL. The errors appeared at the 6 errors of using letters, 15 errors of using word, and 4 errors of using punctuations.